PENGARUH GENDER CHIEF EXECUTIVE OFFICER (CEO), FINANCIAL EXPERTISE CEO, GENDER KOMITE AUDIT, FINANCIAL EXPERTISE KOMITE AUDIT DAN UKURAN KOMITE AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2015-2017 - Afriliana, Nurlisa; Ariani, Nita Erika (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research examines the impact of chief executive officer (CEO) gender, CEO financial expertise, audit committee gender, audit committee financial expertise, and audit committee size on audit delay. The population in this research are the manufacturing companies listed in Indonesia Stock Exchange for period of 2015-2017. The samples in this research study using purposive sampling method, which the number of observations are 39 studies. The technique of data analysis is using multiple linear regression analysis.The result of this research show that CEO gender, CEO financial expertise, audit committee gender, audit committee financial expertise, and audit committee size have affect on audit delay. Partially the research show that (1) CEO gender has an effect on audit delay, (2) the CEO's financial expertise has an effect on the audit delay, (3) the gender audit committee has no effect on audit delay, (4) the financial expertise of the audit committee has no effect on the audit delay, (5) the size of the audit committee influences audit delay.